Correlation and Differences in Lumbopelvic Sagittal Alignment Parameters Between Lumbar Radiographs and Magnetic Resonance Images. Issue 1 (January 2022) - Xu, Chongqing; Yin, Mengchen; Mo, Wen
Study Design: Imaging parameter study. Objective: Though lumbar alignment is better evaluated using standing radiograph than supine magnetic resonance imaging (MRI), few studies have researched this. Our study aimed to observe the correlation and difference in alignment between standing radiograph and supine MRI, and assess whether the change of position affects the lumbopelvic parameters. Methods: We analyzed 105 patients, measuring lumbar lordosis (LL), sacral slope (SS), pelvic tilt (PT), and pelvic incidence (PI). Inter- and intraparameter analyses were performed to identify any difference between standing radiograph and supine MRI. Statistical differences between the lumbopelvic parameters were compared. Results: There was excellent interobserver agreement for each parameter (interclass correlation coefficient > 0.75), and significant differences were observed in each parameter between radiograph and MRI ( P < .05). Strong correlations were noted between the equivalent parameters in radiograph and MRI, both SS and PI were strongly correlated with LL in radiograph and MRI image, both PT and SS were strongly correlated with PI in radiograph and MRI image ( r = −1.0 to −0.5 or 0.5 to 1.0). Conclusion: Supine MRI obviously underestimated the measurements of lumbopelvic sagittal alignment parameters in standing radiograph. Therefore, standing lumbar radiographs should be obtained preoperatively in all surgical patients, not only supine MRI. In addition, we observed that PI was not a constant morphological parameter.